Human OCT2 variant c.808G>T confers protection effect against cisplatin-induced ototoxicity. (March 2015) - Lanvers-Kaminsky, Claudia; Sprowl, Jason A; Malath, Ingrid; Deuster, Dirk; Eveslage, Maria; Schlatter, Eberhard; Mathijssen, Ron HJ; Boos, Joachim; Jürgens, Heribert; am Zehnhoff-Dinnesen, Antionette G; Sparreboom, Alex; Ciarimboli, Giuliano
Aim: Assuming that genetic variants of the SLC22A2 and SLC31A1 transporter affect patients' susceptibility to cisplatin-induced ototoxicity, we compared the distribution of 11 SLC22A2 variants and the SLC31A1 variant rs10981694 between patients with and without cisplatin-induced ototoxicity.Patients & methods: Genotyping was performed in 64 pediatric patients and significant findings were re-evaluated in 66 adults.Results: The SLC22A2 polymorphism rs316019 (c.808G>T; Ser270Ala) was significantly associated with protection from cisplatin-induced ototoxicity in the pediatric (p = 0.022) and the adult cohort (p = 0.048; both: Fisher's exact test). This result was confirmed by multiple logistic regression analysis accounting for age which was identified as a relevant factor for ototoxicity as well (rs316019: OR [G/T vs G/G] = 0.12, p = 0.009; age: OR [per year]: 0.84, p = 0.02).Conclusion: These results identified rs316019 as potential pharmacogenomic marker for cisplatin-induced ototoxicity and point to a critical role of SLC22A2 for cisplatin transport in humans and its contribution to the organ specific side effects of this drug. Original submitted 17 September 2014; Revision submitted 19 December 2014